TANTANGAN TERORISME DI ERA ARTIFICIAL INTELLIGENCE (AI) - Minardi, Minardi (JURNAL ILMU SOSIAL DAN ILMU POLITIK, 2025)
It is undeniable that social media is used for acts of terrorism. However, it does not mean that blocking social media is permissible. So far, the government has emphasized blocking accounts, channels, chat rooms, and posts to prevent acts of terrorism. In addition, by holding content design competitions as a countermeasure to terrorism. The social media problem is not over yet. Artificial Intelligence (AI) has re-emerged as a continuation of social media technology. Artificial Intelligence (AI) comes from algorithms, which come from Big Data that contains digital footprints of social media. However, until now, discourse and research on Artificial Intelligence (AI) and terrorism have still rarely been carried out. Terrorists have used Artificial Intelligence (AI) in carrying out their actions. This study uses a qualitative method with a literature study approach. It aims to provide input to the government regarding the urgency of terrorists who have utilized Artificial Intelligence (AI). In addition, it is a topic of discussion and analysis for law enforcement, academics, and early warning for the community. Terrorists have used Artificial Intelligence (AI) in at least four (4) forms: 1) cyber hacking; 2) sabotage and manipulation; 3) remote attacks; and 4) tutorials and information.